Racism and Trauma: Borderlands, Ambivalent Healing, and Hope - Barros, Pearl Maria ca. 20./21. Jh. (Concilium, 2023)
How might Christian theologies respond to the trauma of racism that wounds the Body of Christ, especially when Christianity has sometimes been used to justify racism? Drawing on theologian Shelly Rambo's assertion that "trauma is an open wound" and Chicana theorist Gloria Anzaldúa's concept of the United States-Mexico border as an "open wound," this article examines the relationship between trauma and racism by focusing on the experiences of Latinx women in the U.S. In particular, it analyzes the way this trauma is connected to the racist trope of "illegality" operative in the U.S. political imagination. Even if they are born in the U.S. or are U.S. citizens, Latinx women are cast as perpetual outsiders. This article asks: What concepts of healing might stem from living in this state of perpetual otherness? And what might they offer Christian theologies attempting to respond to the traumas of racism?